2019
DOI: 10.3390/dj7040111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Digital Protocol for Pre-Surgical Orthopedic Treatment of Cleft Lip and Palate in Newborn Patients: A Pilot Study

Abstract: The aim of this study was to evaluate the accuracy, invasiveness and impact on clinical results of a digital oral impression protocol in the pre-surgical orthopedic treatment (PSOT) of newborn cleft lip and palate (CLP) patients undergoing primary alveolar surgical repair. Six patients were divided, according to impression technique used, into a digital (intraoral scanner (IOS)) and a non-digital (tray and putty (T&P)) group. Parents considered IOS impressions to be less invasive, compared to T&P impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 56 publications
0
31
0
3
Order By: Relevance
“…Después de la selección de los 25 artículos para la revisión narrativa, esta información obtenida se ha clasificado en estudios de cohorte 20%, de revisión sistemática el 4%, estudio de cohorte transversal 20%, estudió observacional 4%, reporte de caso 8%, articulo original 36%, estudio comparativo 4%, ensayo clínico 4%, como se describe en la Figura 2. El proceso de búsqueda y selección de artículos científicos para la revisión sistemática de métodos de obtención de modelos de trabajo o estudio de niños con labio y paladar fisurado Después de la selección de los 25 artículos para la revisión narrativa, esta información obtenida se ha clasificado en estudios de cohorte (Azhari et al, 2021;Dalessandri et al, 2019;Pillai et al, 2021;Thurzo et al, 2022;Zarean et al, 2022), de revisión de literatura el 4% (Shujaat et al, 2022), estudio de cohorte transversal 20% (Burcu Nur Yılmaz et al, 2019;Fomenko et al, 2019;Passucci Ambrosio Eloá Cristina, 2021), estudió observacional 4% (Asquith & McIntyre, 2012), reporte de caso 8% (Jamayet et al, 2018;Krey K.F, 2018), articulo original 8% (Chalmers et al, 2016;El-Ashmawi et al, 2022;Martin et al, 2015;Okazaki et al, 2022;Patel et al, 2019;Ritschl et al, 2018;Salazar-Gamarra et al, 2016;Xepapadeas et al, 2020;Zeidan & Kamiloğlu, 2021), estudio comparativo 4% (Zhu et al, 2016), ensayo clínico 4%(R. R. Kalaskar & Kk, 2021).…”
Section: Resultsunclassified
“…Después de la selección de los 25 artículos para la revisión narrativa, esta información obtenida se ha clasificado en estudios de cohorte 20%, de revisión sistemática el 4%, estudio de cohorte transversal 20%, estudió observacional 4%, reporte de caso 8%, articulo original 36%, estudio comparativo 4%, ensayo clínico 4%, como se describe en la Figura 2. El proceso de búsqueda y selección de artículos científicos para la revisión sistemática de métodos de obtención de modelos de trabajo o estudio de niños con labio y paladar fisurado Después de la selección de los 25 artículos para la revisión narrativa, esta información obtenida se ha clasificado en estudios de cohorte (Azhari et al, 2021;Dalessandri et al, 2019;Pillai et al, 2021;Thurzo et al, 2022;Zarean et al, 2022), de revisión de literatura el 4% (Shujaat et al, 2022), estudio de cohorte transversal 20% (Burcu Nur Yılmaz et al, 2019;Fomenko et al, 2019;Passucci Ambrosio Eloá Cristina, 2021), estudió observacional 4% (Asquith & McIntyre, 2012), reporte de caso 8% (Jamayet et al, 2018;Krey K.F, 2018), articulo original 8% (Chalmers et al, 2016;El-Ashmawi et al, 2022;Martin et al, 2015;Okazaki et al, 2022;Patel et al, 2019;Ritschl et al, 2018;Salazar-Gamarra et al, 2016;Xepapadeas et al, 2020;Zeidan & Kamiloğlu, 2021), estudio comparativo 4% (Zhu et al, 2016), ensayo clínico 4%(R. R. Kalaskar & Kk, 2021).…”
Section: Resultsunclassified
“…A study conducted by Dalessandri et al 28 compared an intraoral scanner (IOS) with the tray and putty method for creating impressions of CLP. They reported that parents considered IOS to be less invasive and clinicians were less stressed with its use.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, intraoral scanner has been gaining acceptance for use in infants for treatment of cleft lip and palate. There have been several reports on single to few cases in infants with cleft lip and palate in the context of developing digital workflows for fabrication of orthopaedic appliances 10,19,20 . Recently Weise et al has reported an evaluation of intraoral scanning in infant to small children with craniofacial malformations 21 .…”
Section: Introductionmentioning
confidence: 99%